Application of mean maximum Young’s modulus value as a new parameter for differential diagnosis of prostate diseases - Nailei Huang; Xinge Cao; Zhong Li; Haoyu Wang; Wei Zhao; Jun Shi (Scientific Reports)
Abstract Transrectal shear wave elastography (T-SWE) can be used non-invasively to diagnose prostate cancer (PCa) and benign prostatic hyperplasia (BPH). The prostate tissue can be viewed as an ellipsoidal sphere with viscoelastic characterization. Linear elastic model has been used to characterize soft tissues, and the simplification of partial characterization provides incomplete information. This retrospective study included 144 suspected prostate disease patients who had completed T-SWE from our hospital. The mean maximum Young’s modulus value (m-Emax) of the maximum transverse section of prostate was obtained by calculating the mean of 12 measured maximum Young’s modulus value (Emax) in the four quadrants. M-Emax was statistically correlated with and good discriminability for PCa and BPH. There was a nonlinear dose-response relationship between m-Emax and PCa risk, as well as between m-Emax and BPH risk. The relationship between m-Emax and prostate disease was consistent with the nonlinear effect showed by tissues as an elastic model in normal physiological activity areas. When stiffness increasing, the stress-strain relationship was approximates linear. M-Emax can be used as an innovative parameter of Young’s modulus value, which represents the stiffness of prostate tissue in T-SWE, and has a good effect in the differential diagnosis of prostate diseases.